Pyloroduodenojejunostomy: A useful alternative for benign gastroduodenal strictures - Shibumon Mundunadackal Madhavan; Smita Chauhan; Sneha Jha; Suneed Kumar; Shakeel Masood (Formosan Journal of Surgery, 2022)
Background: Gastric outlet obstruction is a common condition due to various malignant and benign etiologies. Benign gastric outlet obstruction has been managed surgically by gastric resection or drainage procedures. Pyloroduodenojejunostomy (PDJ) is an old surgical procedure with very few descriptions in the literature and is rarely performed now. We present our experience of six cases of Roux-en-Y PDJ performed for benign gastroduodenal strictures causing gastric outlet obstruction. Materials and Methods: Prospective study of patients who underwent Roux-en-Y PDJ for benign gastroduodenal obstruction in the department of Surgical Gastroenterology in a teaching hospital in Northern India from January 2017 to December 2019. Side-to-side pyloroduodenojejunostomy was done with a Roux-en-Y limb of jejunum along with side-to-side jejunojejunostomy. A feeding jejunostomy was added in patients who were nutritionally poor. No vagotomy was performed. Results: Four male and two female patients with median (range) age of 42 (37–61) years underwent PDJ. There were no major postoperative complications in the study group. Etiology of benign strictures was tuberculosis in two patients and peptic in four. On mean (standard deviation [SD]) follow-up of 19.5 (5.12) months, all the patients were symptom-free. The mean (SD) weight gain was 10 (3.40) kg. Conclusion: Roux-en-Y PDJ is a useful alternative in the management of surgically difficult cases of benign gastroduodenal strictures with low morbidity and good outcome.